ANALISA BIAYA DAN PENJADWALAN PADA PROYEK PENATAAN BANGUNAN KAWASAN STRATEGIS MASJID RAYA SUMBAR KOTA PADANG - Nasrul Nasrul; Wilda Yurma (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
In the implementation of the Strategic Area Building Structuring Project for the Great Mosque of West Sumatra, Padang City, it was carried out with careful planning so that the project was completed in accordance with a predetermined time period. In fact, projects always encounter obstacles so that the project does not go according to plan. Therefore we are required to be able to control costs and scheduling so that the project implementation goes according to plan. Many obstacles in the field result in delays in work in the field. In the contract document, sanctions are given with a stipulation of 1/1000 of the contract price (before VAT), referring to the PUPR Ministerial Regulation Number 31 / PRT / M / 2015, attachment I of standards and guidelines for procurement of single construction work SSUK article 66.4 letter c. And applying the CPM method in rescheduling the building arrangement project in the strategic area of the Grand Mosque in West Sumatra, Padang city by using the CPM method, it was obtained 203 days to complete the work. While the scheduling planned by the executor of the 210 day job.